2017
DOI: 10.4236/jep.2017.88058
|View full text |Cite
|
Sign up to set email alerts
|

Highway Infrastructure, Protected Areas, and Orchid Bee Distribution and Conservation in the Brazilian Amazon

Abstract: Scientists regularly lament that development and habitat destruction in once isolated and distant areas are promoting species extinction before species can even be known by science. In the Brazilian Amazon, the government's Plan for Growth Acceleration in part involves major improvements and expansion of highways. Such infrastructure has long been linked to the main causes of deforestation in this region. It is essential for scientists to assess where to target biodiversity collections in relation to the locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…A recent study addressing digital and non-digital records of orchid bees in Brazilian Amazon, showed that in >50% of collection places it is known the presence of just one orchid bee species, indicating that the majority of the locations sampled represent casual collections (Oliveira et al, 2017). The species Euglossa imperialis and Exaerete frontalis categorized in this work as rare species, are actually very common, being collected in most inventories carried out in Amazonia (e.g.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A recent study addressing digital and non-digital records of orchid bees in Brazilian Amazon, showed that in >50% of collection places it is known the presence of just one orchid bee species, indicating that the majority of the locations sampled represent casual collections (Oliveira et al, 2017). The species Euglossa imperialis and Exaerete frontalis categorized in this work as rare species, are actually very common, being collected in most inventories carried out in Amazonia (e.g.…”
Section: Discussionmentioning
confidence: 75%
“…The Amazon basin contains about 127 species of euglossine bees (Nemésio and Silveira, 2007), and in this study, was possible to record more than 40% of this species analyzing historical data in the BEC. Nevertheless, we emphasize the importance of distributing more sampling sites, especially in the state of Maranhão, given the rapid disappearance of natural vegetation and few conservation units in the state (Oliveira et al, 2017), but also in southwestern portion of the state of Pará. Additionally, is necessary to adopt standardized studies with orchid bees in future sampling in the region.…”
Section: Discussionmentioning
confidence: 97%
“…Large projects were implemented in the country by that time (Hall 1989;Mahar 1979), e.g. the construction of large highways such as the Transamazônica (Oliveira et al 2017). This development period was influenced by the creation of the SPVEA (Superintendence for the Amazon Economic Valuation Plan-Superintendência do Plano de Valorização Econômica da Amazônia) and the PDA (Development Plan of the Amazon-Plano de Desenvolvimento da Amazônia), which stemmed out from the 1 st PND (National Development Plan-Plano Nacional de Desenvolvimento).…”
Section: Historical Political and Socioeconomic Context Of Forest Lomentioning
confidence: 99%